2021
DOI: 10.1002/open.202000317
|View full text |Cite
|
Sign up to set email alerts
|

On the Heterogeneous Nature of Cisplatin‐1‐Methyluracil Complexes: Coexistence of Different Aggregation Modes and Partial Loss of NH3 Ligands as Likely Explanation

Abstract: The conversion of the 1 : 1-complex of Cisplatin with 1-methyluracil (1MeUH), cis-[Pt(NH 3) 2 (1MeU-N3)Cl] (1 a) to the aqua species cis-[Pt(NH 3) 2 (1MeU-N3)(OH 2)] + (1 b), achieved by reaction of 1 a with AgNO 3 in water, affords a mixture of compounds, the composition of which strongly depends on sample history. The complexity stems from variations in condensation patterns and partial loss of NH 3 ligands. In dilute aqueous solution, 1 a, and dinuclear compounds cis-[(NH 3) 2 (1MeU-N3)Pt(μ-OH)Pt(1MeU-N3)(N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…by iodide, we have later demonstrated that it is possible to convert cis-[Pt (NH 3 ) 2 (nb)X] compounds in reasonable yields readily into trans-[Pt(NH 3 )(nb)X 2 ] [163]. Examples with nb being purine bases have likewise been obtained this way [197], as have been two species containing the pyrimidine base 1MeU [49,73].…”
Section: Examples Formation and Potential Relevancementioning
confidence: 89%
See 4 more Smart Citations
“…by iodide, we have later demonstrated that it is possible to convert cis-[Pt (NH 3 ) 2 (nb)X] compounds in reasonable yields readily into trans-[Pt(NH 3 )(nb)X 2 ] [163]. Examples with nb being purine bases have likewise been obtained this way [197], as have been two species containing the pyrimidine base 1MeU [49,73].…”
Section: Examples Formation and Potential Relevancementioning
confidence: 89%
“…Yields of the 1:1-complexes are frequently moderate or low due to concomitant formation of the corresponding bis (nucleobase) complex, and the possibility of subsequent secondary reactions of either species with the remaining available Pt starting compound [48]. Occasionally, detour reactions to obtain the desired mono(nucleobase) species can be advantageous [49]. Binding sites of the model nucleobase to Pt II usually follow expectations [50], as outlined above.…”
Section: Examplesmentioning
confidence: 99%
See 3 more Smart Citations